Counterinsurgency Operations in the Second District of Sorsogon: Basis for Sustainable Development - Santos, Santos; Macabeo, Manny (JPAIR Multidisciplinary Research, 2024)
Throughout history, insurgency has been a persistent phenomenon, its origins stemming from various factors such as political, economic, social, and ethnic grievances that drive certain factions or individuals to take up arms in resistance. This study determined the status of COIN operations in terms of Legal basis, Manpower, Financial resources, Logistical resources, and Accomplishments from 2021 to 2023. Likewise, this evaluates the COIN operations of the unit along with the conduct of Internal Security operations, Intelligence operations, and Police Community Affairs and development to determine challenges that were encountered by the personnel. The respondents of the study are the PNP personnel, barangay officials, and former rebels. The counterinsurgency framework presents a comprehensive and strategic approach to addressing insurgency threats, with the potential to significantly enhance the conduct of counterinsurgency operations. The findings underscore both the acknowledged strengths and identified areas for enhancement within police operations, as reported by respondents from the PNP. This shows a widespread acknowledgment of the pivotal role of the ISO in upholding internal security and addressing insurgent challenges. It signifies a mutual understanding among diverse stakeholders, encompassing barangay officials, former rebels, and law enforcement personnel, regarding the necessity of proactive strategies to prevent, interrupt, and counter-insurgency operations within impacted localities. Overall, the proposed framework offers a promising strategy for countering insurgency threats and advancing the goals of peace, stability, and security in affected regions.